Comparison of Outcomes Following Anterior vs Posterior Fusion Surgery for Patients With Degenerative Cervical Myelopathy: An Analysis From Quality Outcomes Database. Issue 4 (8th May 2018) - Asher, Anthony L; Devin, Clinton J; Kerezoudis, Panagiotis; Chotai, Silky; Nian, Hui; Harrell Jr., Frank E; Sivaganesan, Ahilan; McGirt, Matthew J; Archer, Kristin R; Foley, Kevin T; Mummaneni, Praveen V; Bisson, Erica F; et al.
Abstract: BACKGROUND: The choice of anterior vs posterior approach for degenerative cervical myelopathy that spans multiple segments remains controversial. OBJECTIVE: To compare the outcomes following the 2 approaches using multicenter prospectively collected data. METHODS: Quality Outcomes Database (QOD) for patients undergoing surgery for 3 to 5 level degenerative cervical myelopathy was analyzed. The anterior group (anterior cervical discectomy [ACDF] or corpectomy [ACCF] with fusion) was compared with posterior cervical fusion. Outcomes included: patient reported outcomes (PROs): neck disability index (NDI), numeric rating scale (NRS) of neck pain and arm pain, EQ-5D, modified Japanese Orthopedic Association score for myelopathy (mJOA), and NASS satisfaction questionnaire; hospital length of stay (LOS), 90-d readmission, and return to work (RTW). Multivariable regression models were fitted for outcomes. RESULTS: Of total 245 patients analyzed, 163 patients underwent anterior surgery (ACDF-116, ACCF-47) and 82 underwent posterior surgery. Patients undergoing an anterior approach had lower odds of having higher LOS ( P < .001, odds ratio 0.16, 95% confidence interval 0.08-0.30). The 12-mo NDI, EQ-5D, NRS, mJOA, and satisfaction scores as well as 90-d readmission and RTW did not differ significantly between anterior and posterior groups. CONCLUSION: Patients undergoing anterior approaches for 3 to 5 level degenerative cervical myelopathy had shorter hospital LOS compared to those undergoing posterior decompression and fusion. Also, patients in both groups exhibited similar long-term PROs, readmission, and RTW rates. Further investigations are needed to compare the differences in longer term reoperation rates and functional outcomes before the clinical superiority of one approach over the other can be established.